Evaluating the Effectiveness of an Autism-Specific Workplace Tool for Employers: A Randomised Controlled Trial - Scott, Melissa; Falkmer, Marita; Falkmer, Torbjorn; Girdler, Sonya (Springer New York LLC, 2018)
A randomised controlled trial evaluated the effectiveness of the Integrated Employment Success Tool (IEST™) in improving employers’ self-efficacy in modifying the workplace for individuals on the autism spectrum. Employers (N = 84) were randomised to the IEST™ or support as usual groups. Measurements of self-efficacy, knowledge and attitudes towards disability in the workplace were obtained at baseline and post-test. Results revealed a significant improvement in self-efficacy within the IEST™ group between baseline and post-test (p = 0.016). At post-test, there were no significant differences between groups in relation to self-efficacy in implementing autism-specific workplace modifications and employer attitudes towards disability in the workplace. Given the lack of significant outcomes, further research is needed to determine the effectiveness of the IEST™ for employers.